Bacillus subtilis no tratamento de mudas de bananeira infectadas por fitonematoides - da Silva Araújo, Jardel Jean; Silva Muniz, Maria de Fátima; Moura Filho, Gilson; da Silva Rocha, Fernando; da Cunha e Castro, José Mauro (Revista Ceres, 2025)
The use of healthy propagative plant material is an important management method for nematodes in banana crops (Musa spp.), once it prevents the introduction of nematodes in non-infested areas. The aim of this work was to evaluate the effect of the bio-nematicide Nemathel® (Bacillus subtilis) on Terra banana plantlets cv. Comprida infected with a mixed population of Radopholus similis, Meloidogyne spp., Pratylenchus spp., and Helicotylenchus spp. Different doses of Nemathel® (50, 100, 150, 200, and 250 mL/10 L water) were tested in addition to the positive (nematicide) and negative (water) treatments. The plantlets were immersed in each treatment for 30 min and subsequently, planted in pots containing sterilized soil in greenhouse. The evaluation was performed four months later. Dosages of 200 and 250 mL of Nemathel®/10 L in water showed the greatest reduction of nematode populations in roots and rhizomes.